Profil Pengukuran Fleksibilitas Lengan dan Bahu Pada Siswa SMK Negeri 1 Cikalong Kabupaten Tasikmalaya - Ramadhan, Alwi Awal; Risma, Risma; Erlina, Terra (Jurnal Keolahragaan, 2023)
This study aims to measure the flexibility of the arms and shoulders. The research method is surveys and test implementation techniques which are then measured. The research location is at SMK Negeri 1 Cikalong, Tasikmalaya Regency. The samples involved were students who took part in volleyball as many as 25 students. Sampling by means of total sampling. The measurement tools used are the static flexibility test-shoulder and wrist. Processing and analysis of statistical data is SPSS series 24 and percentages. The result is 1 person with a percentage value of 4% (less). 11 people the percentage value is 44% (moderate). 8 people with a percentage score of 32% (good). 4 people with a percentage score of 16% (very good). 1 person percentage value 4% (perfect). The overall average is 8.61. Conclusion: Male students at SMK Negeri 1 Cikalong, Tasikmalaya Regency, after going through a test measuring the flexibility of their arms and shoulders, are included in the average or good category.Penelitian ini bertujuanpengukuran fleksibilitas lengan dan bahu. Metode penelitian yaitu surveidan teknik pelaksanaan tes yang selanjutnya dilakukan pengukuran. Lokasi penelitian di SMK Negeri 1 Cikalong Kabupaten Tasikmalaya. Sampel yang terlibat yaitu siswa yang mengikuti olahraga bolavoli sebanyak 25 siswa. Pengambilan sampel dengan cara total sampling.Alat ukur yang diterapkan adalah static flexibility test-shoulder and wrist. Pengolahan dan analisis data statistika adalah SPSS serie 24 dan persentase. Hasilnya 1 orang nilai persentase 4 % (kurang).11 orang nilai persentase 44 % (sedang).8 orang nilai persentase 32 % (baik).4 orang nilai persentase 16 % (baik sekali).1 orang nilai persentase 4 % (sempurna). Rata-ratakeseluruhan yaitu 8,61. Kesimpulan: Siswa putra SMK Negeri 1 Cikalong Kabupaten Tasikmalaya setelah melalui tes pengukuran fleksibilitas lengan dan bahu termasuk pada kategori average atau baik